Adaptive Liquid Lens and Sunlight Redirection. (June 2014) - Heinzelmann, Florian; Bristogianni, Telesilla; Teuffel, Patrick
The paper describes a novel system to alter and redirect sunlight under large roofs with the help of a liquid lens system. Focus lies on the computational design, testing, measurement and evaluation of the performance of a physical prototype. The results in terms of daylight and illumination of the interior, as well as the possibility for sunlight redirection, lead to an array of adaptive natural light spotlights, which are rather promising. The journal article is an extension of previously reported work[1].